Numerical Simulation of the Influence of Geological CO2 Storage on the Hydrodynamic Field of a Reservoir - Zhaoxu Mi; Fugang Wang; Zhijie Yang; Xufeng Li; Yujie Diao; Xin Ma; Hailong Tian (Geofluids)
CO2 geological storage in deep saline aquifers is an effective way to reduce CO2 emissions. The injection of CO2 inevitably causes a significant pressure increase in reservoirs. When there exist faults which cut through a deep reservoir and shallow aquifer system, there is a risk of the shallow aquifer being impacted by the changes in reservoir hydrodynamic fields. In this paper, a radial model and a 3D model are established by TOUGH2-ECO2N for the reservoir system in the CO2 geological storage demonstration site in the Junggar Basin to analyze the impact of the CO2 injection on the deep reservoir pressure field and the possible influence on the surrounding shallow groundwater sources. According to the results, the influence of CO2 injection on the reservoir pressure field in different periods and different numbers of well is analyzed. The result shows that the number of injection wells has a significant impact on the reservoir pressure field changes. The greater the number of injection wells is, the greater the pressure field changes. However, after the cessation of CO2 injection, the number of injection wells has little impact on the reservoir pressure recovery time. Under the geological conditions of the site and the constant injection pressure, although the CO2 injection has a significant influence on the pressure field in the deep reservoir, the impact on the shallow groundwater source area is minimal and can be neglected and the existing shallow groundwater sources are safe in the given project scenarios.